Preventing youth substance abuse: science-based programs for children and adolescents - Tolan, Patrick H.; Tolan, Patrick H. (American Psychological Association, 2007)
Preventing substance abuse : an overview / José Szapocznik, Patrick Tolan, Soledad Sambrano and Seth J. Schwartz -- Key concepts for prevention research and practice -- Development in childhood and adolescence : implications for prevention research and practice / Marija G. Dunn and Ada C. Mezzich -- Research to practice : bringing effective prevention to every community / Paul Brounstein, Steve Gardner, and Thomas E. Backer -- Interventions for preschool children : ages 3-5 -- Incredible years parent and teacher training series : a head start partnership to promote social competence and prevent conduct problems / Carolyn Webster-Stratton, and M. Jamila Reid -- Project star : early intervention with preschool children and families for the prevention of substance abuse / Ruth Kaminski and Beth Stormshak -- Interventions for elementary school children : ages 6-8 -- Schools and families educating children (safe children) : a preventive intervention for early elementary school children / Deborah Gorman-Smith, Patrick H. Tolan, David B. Henry, Elena Quintana, Kelly Lutovsky, and Amy Lenventhal -- The early risers "skills for success" program : an early-age-targeted intervention for preventing conduct problems and substance abuse in aggressive elementary school children / Gerald J. August, George M. Realmuto, Michael L. Bloomquist, and Joel M. Hetkner -- The strengthening families program (SFP) : an evidence-based, multi-cultural family skills training program / Karol L. Kumpfer, Rose Alvarado, Connie Tai, and Henry O. Whiteside -- Interventions for preadolescent children and young adolescents : ages 9-14 -- The coping power program : preventive intervention at the middle school transition / John Lochman, Karen Wells and Maureen Murray -- Familias unidas : a systemic, parent-centered approach to preventing problem behavior in Hispanic adolescents / Hilda Pantin, Seth J. Schwartz, J. Douglas Coatsworth, Summer Sullivan, Ervin Briones and José Szapocznik -- Conclusions -- Developmental opportunities for prevention of substance abuse / Patrick Tolan, Jose Szapocznik, Soledad Sambrano